A COMPARATIVE ANALYSIS OF THE RELATIONSHIP BETWEEN PARENTING STYLES AND STUDENTS’ MORALITY - Hafidz Yuliansyah; Nurul Hidayah; Zumratul Azka; Ichsan Ichsan; Sibawaihi Sibawaihi (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to analyze the influence of parenting styles on student morality at Madrasah Mu’allimin Yogyakarta, addressing the gap in empirical research regarding the causal relationship between parental approaches and moral development in Islamic educational settings. Employing a comparative quantitative design, the research compared the effects of democratic, authoritarian, and permissive parenting styles on the moral character of 12th-grade students. Data were collected through standardized questionnaires and analyzed using descriptive statistics, normality and homogeneity tests, one-way ANOVA, and Tukey HSD post-hoc analysis. The findings revealed that students raised with a democratic parenting style exhibit the highest mean moral scores, followed by those with authoritarian and permissive backgrounds. Statistical analysis confirmed a significant difference in moral outcomes between democratic and permissive parenting styles (p < 0.05), while differences between democratic-authoritarian and authoritarian-permissive styles were not statistically significant. The democratic style’s effectiveness was attributed to its balance of emotional support and rational behavioral expectations, fostering internalization of moral values and student autonomy. Conversely, permissive parenting correlated with weaker moral boundaries, and authoritarian approaches rely on obedience without deep moral comprehension. These results underscored the critical role of parenting in shaping student morality, highlighting the democratic style as the most conducive to moral development. Implication of this study that parents and educational institutions prioritized democratic parenting strategies to nurture morally upright future generations, with implications for policy and parental education programs in Islamic schools.